Socioeconomic and Demographic Contexts of Brazilian and International University Students Regarding the Use of Dental Services - Cosmo Helder Ferreira da Silva; Edmara Chaves Costa; Ana Caroline Rocha de Melo Leite; Vânia Barbosa do Nascimento (International Journal of Dentistry)
This article characterizes the different socioeconomic and demographic contexts regarding the use and access to dental services by Brazilian and African students at a Brazilian university of international nature. This is a cross-sectional, analytical, observational study with a quantitative approach, with data produced by 350 students from a public university in the state of Ceará. Sociodemographic and economic factors, participation in educational activities, self-perception of oral health, and use of dental services by academics were analyzed. The results obtained indicated that of the university students participating in the study, 74.0% had already used dental services, of which 57.43% were Brazilian and 42.57% international. There was a significant association between being a Brazilian academic and having already used dental services, having an income less than or equal to the minimum wage, and having used the public dental service. The determination of the prevalence of use of dental services and the different contexts of university students can assist in planning future actions in oral health that prioritize groups of university students with greater difficulties in the use and access of these services.